FAKTOR-FAKTOR YANG MEMPENGARUHI KEPERCAYAAN NASABAH PENGGUNA CASH DEPOSIT MACHINE (CDM) (STUDI BNI SYARIAH CABANG KOTA BENGKULU) - Febriansyah, Erwin; Ramayuniarti, Feby (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2016)
The problems studied in this study, namely whether the factors that affect customer confidence in the user cash deposit machine. The purpose of this study is To determine what factors that affect customer confidence in the user cash deposit machine. This research has been done in November to complete. To solve the problem deeply and thoroughly, the researcher uses case study and field study method which is direct observation and interview to BNI Syariah customer using cash deposit machine, then the data is collected, described and analyzed for Answer the problem. From the results of this study concluded that the factors that influence customer service that is technology orientation, poor access speed in access network of CDM, reputation that is reputation of bank itself lack of socialization to usage of cash deposit macine to customer and perceived risk or risk There is still a lot in the use of cash deposit machine, so the customer's trust is still less to use cash deposit machine / CDM.Keywords: Cash Deposit Machine, Customer Trust